Effects of the HeartMate II Left Ventricular Assist Device as Observed by Serial Echocardiography. Issue 5 (11th January 2013) - Chapman, Carrie B.; Allana, Salman; Sweitzer, Nancy K.; Kohmoto, Takushi; Murray, Margaret; Murray, David; Johnson, Maryl; Rahko, Peter S.
<x xml:space="preserve">Abstract</x> Background The HeartMate II is the most frequently used left ventricular assist device (LVAD) in patients with end‐stage heart failure. There is a paucity of data regarding its longitudinal cardiac effects, particularly that on diastole. Methods This retrospective study was an evaluation of echocardiograms preoperatively and at 3, 6, and 12 months postoperatively in patients with a HeartMate II. Measurements included left ventricle (LV) dimensions, ejection fraction (EF), right ventricle (RV) size and function, parameters of diastolic function, and an analysis of mitral regurgitation (MR), tricuspid regurgitation (TR), aortic insufficiency (AI), and aortic valve thickening. Results Forty‐seven patients were evaluated. LV dimensions decreased but EF, RV size, and RV function were unchanged. Right ventricular systolic pressure (RVSP) and diastolic parameters including mitral inflow E/A, deceleration time (DT), pulmonary vein inflow, left atrial size, and overall diastolic grade improved. LV relaxation measured by tissue Doppler (e') was unchanged and the E/e' ratio was also unchanged. Regarding valve function, MR decreased, TR was unchanged, and the aortic valve became increasingly thickened with increased AI severity. Conclusions The HeartMate II unloads the LV as shown by decreased LV size, decreased MR, reduced RVSP, and improved patterns of mitral inflow. However, neither systolic function nor diastolic relaxation improves in this cohort. RV size and function also remain unchanged. The aortic valve shows increased thickening and AI likely from valve leaflet fusion. These results provide detailed functional and hemodynamic information regarding the longitudinal effects of the HeartMate II.